English: Validitas dan Praktikalitas E-modul Fisika - Endang Aldilla; Usmeldi (Postgraduate, University of Mataram, 2024)
The development of science and technology in the 21st century requires skills for an individual to be able to compete, which are called 4C skills. Initial studies show that students' 4C skills still need to be improved. The physics e-module based on the orientation, identify, discussion, and engage in behavior model is an important aspect that supports improving students' 21st century skills. This research aims to determine the validity and practicality of e-modules. The instrument used to collect data was a validity and practicality test questionnaire. The physics e-module based on the orientation identify, discussion, decision, and engage in behavior can be used in the learning process. Judging from the results of validity and practicality, the physics E-module based on the orientation, identify, discussion, decision, and engage in behavior model to improve students' 21st century skills has valid and practical criteria with an average validity value (Aiken's value) of 0, 93 with valid criteria. The teacher's practicality score is 89.6% with very practical criteria and the students' practicality is 87.4% with very practical criteria. This means that e-modules can be applied to physics learning and in theory can improve students' 21st century competency abilities.